Realization of PPPoE Fast Forwarding in Distributed ACR - Gaowei Wang; Jixing Zhang; Zhihui Xiao; Yishan Chen (Dianxin kexue)
The large-scale involvement of the large-scale access convergence router was described for the significance of application of multiple access networks.In the background of network convergence,the role of ACR in the network was analyzed.Based on the thought of forwarding and control element separation（ForCES）of distributed system, the PPPoE protocol principle and process were analyzed, and the PPPoE access technology was achieved in ACR.The test results show that,the implementation of PPPoE based on a distributed system can meet the requirement of large-scale access application scene,and ACR can support high bandwidth for thousands of concurrent.